Finger Relaxation Technique As A Non-Pharmacological Intervention In Nursing Care - Naomi Malaha; Rezqiqah Aulia Rahmat; Rizki Andita Noviar (International Journal of Health Sciences, 2026)
Relaxation is a non-pharmacological intervention that is effective in reducing anxiety and physiological tension. Finger relaxation techniques relaxation the finger relaxation technique is a simple method that utilizes controlled touch and breathing stimulation to reduce stress responses. This study aims to analyze the effectiveness of the finger relaxation technique as a non-pharmacological intervention in nursing care to reduce patient anxiety. The study used a quasi-experimental design with a pretest - posttest approach. without control group. The sample consisted of 35 patients with mild to moderate anxiety. Anxiety was measured using the Hamilton Anxiety Rating Scale (HARS). The results showed a significant decrease in anxiety scores from 21.4 ± 4.2 to 13.2 ± 3.8 (p < 0.001). It was concluded that finger relaxation techniques were effective as a nursing intervention in reducing patient anxiety.